PEMANFAATAN DAN PENINGKATAN PENGGUNAAN MOBILE BANKING PT. BANK RAKYAT INDONESIA (PERSERO), TBK., DI MASA COVID 19 - Khalila Khasmier Bastian Putri (2021)
With the development of the times, the use of mobile banking has become a very popular way of banking transactions. The method of transacting only using a smartphone without having to leave the house is very helpful during this COVID-19 pandemic. In general, almost all banks have mobile banking services. Bank BRI offers BRImo with attractive features and is very easy to use for its customers according to their respective needs. The purpose of this study was to determine customer interest in using mobile banking with the influence of service quality and convenience obtained as well as comparisons of mobile banking users before and after COVID-19. The influence of service quality is input from customers for BRI in innovating so that it is increasingly in demand by the public. BRI provides a new breakthrough by updating the appearance and services of BRImo that are more user friendly by combining the functions of internet banking, mobile banking and electronic money services in one hand. The results of the writing based on the questionnaire distributed through the google form show that the mobile banking facility is very beneficial and easy for customers, especially during the COVID-19 pandemic. The number of users and usage of BRImo has increased by 660% in the last 1 year, because it can help with daily transaction needs, but in its service BRI is expected to immediately develop applications on all types of smartphones because some BRImo cannot be accessed via Apple smartphones and improvements to the system OTP code via sms so that the OTP code sent is ensured to enter the user's sms.